Controlled formation of uniform nanoshells of manganese oxide and their potential in lithium ion batteries. Issue 19 (20th February 2017) - Liu, Xiao-Chan; Piao, Jun-Yu; Bin, De-Shan; Zhang, Tian-Qi; Duan, Shu-Yi; Wu, Zi-Xiao; Cao, An-Min; Wan, Li-Jun
Abstract : Uniform nanoshells of manganese oxides have been successfully prepared by controlling their growth kinetics in solution. Abstract : Uniform nanoshells of manganese oxides have been successfully prepared by controlling their growth kinetics in solution. The prepared manganese oxides show promising electrochemical performance when used as an anode material in lithium ion batteries.